Insight into the Role of the STriatal-Enriched Protein Tyrosine Phosphatase (STEP) in A2A Receptor-Mediated Effects in the Central Nervous System - Domenici, Maria Rosaria; Mallozzi, Cinzia; Pepponi, Rita; Casella, Ida; Chiodi, Valentina; Ferrante, Antonella; Popoli, Patrizia (Frontiers in Pharmacology, 2021)
The STriatal-Enriched protein tyrosine Phosphatase STEP is a brain-specific tyrosine phosphatase that plays a pivotal role in the mechanisms of learning and memory, and it has been demonstrated to be involved in several neuropsychiatric diseases. Recently, we found a functional interaction between STEP and adenosine A2A receptor (A2AR), a subtype of the adenosine receptor family widely expressed in the central nervous system, where it regulates motor behavior and cognition, and plays a role in cell survival and neurodegeneration. Specifically, we demonstrated the involvement of STEP in A2AR-mediated cocaine effects in the striatum and, more recently, we found that in the rat striatum and hippocampus, as well as in a neuroblastoma cell line, the overexpression of the A2AR, or its stimulation, results in an increase in STEP activity. In the present article we will discuss the functional implication of this interaction, trying to examine the possible mechanisms involved in this relation between STEP and A2ARs.